MANAJEMEN STRES KERJA DAN INTERVENSI ERGONOMIS UNTUK GEJALA EKSTREMITAS ATAS TERKAIT PEKERJAAN - Elza Rachma Fadilah; Susilawati (CV. ADIBA AISHA AMIRA, 2023)
In practice, secondary prevention of work-related upper extremity symptoms (WRUE) generally targets biomechanical risk factors. Psychosocial risk factors have also been shown to play an important role in the development of WRUE symptom severity and future disability. Addition of a stress management component to a biomechanically focused intervention may result in greater improvement in WRUE symptoms and functional limitations than to an intervention on biomechanical risk factors alone. Seventy office workers with WRUE symptoms were randomly assigned to the ergonomics intervention (workplace assessment and modification and stretching exercises) or the combined ergonomics and work stress intervention group (ergonomics intervention plus two 1-hour workshops on identifying and managing stress at work.). Baseline, 3 and 12-month follow-up measures of observed and self- reported ergonomic risk, job stress, pain, symptoms, functional limitations, and general physical and mental health were obtained from all participants. While both groups experienced significant reductions in pain, symptoms, and functional limitations from baseline to three months with continued improvement for up to 12 months after baseline, no significant between-group differences were observed for any outcome measures. The findings indicated that the two-session additional occupational stress management component did not significantly improve the short-term or long-term improvements brought about by ergonomic intervention alone